스타크래프트에 대한 담화분석;그레마스의 구조생성기호학을 중심으로 - 박태순; Park, Tae-Soon (한국콘텐츠학회 논문지, 8(7), 2008)
This paper tried to analyze Starcraft's multiplay by using especially Greimas's theory of discourse. Greimas's theory of semiotics is known as a useful tool of analyzing non-verbal text as well as verbal text. The discourse of Starcraft is continuously made by subject and anti-subject. This characteristic of discourse- not given completely made- is the prominent difference from discourses made from other media. The subject and anti-subject, as actively crossing the position of enunciator and enunciatee each other, dynamically make and complete the discourse. 그레마스의 기호학은 언어텍스트뿐만 아니라 비언어텍스트의 분석에 유용한 것으로서, 특히 담화구조와 관련된 이론을 통하여 스타크래프트의 멀티플레이를 분석해보았다. 스타크래프트의 담화는 그것이 완성되어 주어진 담화가 아니라는 점에서 다른 매체의 담화와는 두드러지게 다른 특성들을 보여주는데, 가장 대표적인 것이 담화를 생산해가고 있는 주체와 반주체라는 존재였다. 이들은 수동적인 존재가 아니며 능동적으로 발화자, 피발화자의 위치를 교차시키며 역동적인 담화를 생성해낸다.